2020
DOI: 10.1016/j.ymthe.2019.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Timeless-Stimulated miR-5188-FOXO1/β-Catenin-c-Jun Feedback Loop Promotes Stemness via Ubiquitination of β-Catenin in Breast Cancer

Abstract: MicroRNAs (miRNAs) play an essential role in the self-renewal of breast cancer stem cells (BCCs). Our study aimed to clarify the role of proto-oncogene c-Jun-regulated miR-5188 in breast cancer progression and its association with Timeless-mediated cancer stemness. In the present study, we showed that miR-5188 exerted an oncogenic effect by inducing breast cancer stemness, proliferation, metastasis, and chemoresistance in vitro and in vivo. The mechanistic analysis demonstrated that miR-5188 directly targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…However, it is highly expressed in colon cancer and significantly correlated with lymphatic metastasis, satellite metastasis and TNM stage (Top et al, 2016;Ozturk et al, 2017). TIMELESS plays a crucial role in the self-renewal process of breast CSCs and interacts with Sp1/c-jun to induce miR-5188 expression by promoting c-jun-mediated transcription, thus promoting breast cancer progression (Zou et al, 2020). Our research also has the following limitations.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is highly expressed in colon cancer and significantly correlated with lymphatic metastasis, satellite metastasis and TNM stage (Top et al, 2016;Ozturk et al, 2017). TIMELESS plays a crucial role in the self-renewal process of breast CSCs and interacts with Sp1/c-jun to induce miR-5188 expression by promoting c-jun-mediated transcription, thus promoting breast cancer progression (Zou et al, 2020). Our research also has the following limitations.…”
Section: Discussionmentioning
confidence: 92%
“…[12][13][14] Recent studies suggested the powerful function of miR-5188 in cancer progression. 15,16 However, the biological effects of miR-5188 in glioma remain insufficiently understood.…”
Section: Introductionmentioning
confidence: 99%
“…C-Jun is an effector of many important signaling pathways like MAPK signaling and Wnt/β-catenin signaling, and has vital roles in the regulation of cell growth, proliferation, differentiation, and apoptosis 40 . As a well-studied transcription factor, c-Jun can regulate the transcription of several miRNAs through binding to their promoter regions, thereby promoting cancer progression 41,42 . Our study has demonstrated that miR-4476 activates Wnt/β-catenin signaling and upregulates c-Jun expression, which, in turn, enhances the expression of miR-4476.…”
Section: Discussionmentioning
confidence: 99%